Efektivitas Pijat Ibu Terhadap Kualitas Tidur Ibu Hamil - Sri Wardini Puji Lestari; Zulfa rufaida (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Sleep disorders are complaints that often occur during pregnancy. Decreased sleep quality, namely reduced sleep duration in pregnant women, is a form of sleep disorder. The effect that occurs in pregnant women who experience sleep disorders is that it reduces the quality of life of pregnant women and affects the growth and development of the fetus they are carrying. One of the non-pharmacological therapies that can improve the sleep quality of pregnant women is pregnancy massage. The aim of this research is to determine the effectiveness of maternal massage on the sleep quality of pregnant women at the UPTD Community Health Center Bangsal Mojokerto. Research method, descriptive Quasi Experiment. The variables used are maternal massage and sleep quality of pregnant women. The population is pregnant women who visit the Bangsal District Health Center. Mojokerto, a sample of 30 respondents for research instruments using the PSQI questionnaire, data analysis using the Mc Nemar statistical test. The results of the study showed that before being given massage, 23 mothers (76.7%) experienced sleep quality in the poor category. After being given a massage, 29 mothers (96.7%) experienced sleep quality in the good category. The results of the Match Pairs Test statistical test showed that after the massage intervention the mother had a p value = 0.031 or p < ?=0.05. The conclusion from this research is that maternal massage is effective in significantly improving the sleep quality of pregnant women. So it is hoped that health workers will always socialize the benefits of maternal massage